MEDIASI IN COURT UNTUK MEWUJUDKAN KEPASTIAN HUKUM BERDASARKAN WIN –WIN SOLUTION - Anita Afriana (Universitas Borneo Tarakan, 2020)
ABSTRACT Basically, same with the civil settlement in the District Court, peace in thesettlement of bankruptcy cases is required to be implemented. The article of130 of HIR / 154 HIR concerning the obligation to reconcile the two sides havebeen concreted through Perma No 1, year 2016. However, this Perma can’t beapplied to the settlement of bankruptcy cases in the Commercial Court. This study want to know the juridical reasons the peace achieved through Mediation In Court based on Perma no. 1 of 2016 can’t be applied in the settlement of bankruptcy disputes in the Commercial Court and the juridical consequences that distinguish between the peace achieved through mediation in Court and the bankruptcy proceedings and PKPU related to certainty as the purpose of law Peace institutions through Perma No1, year 2016 pursued by means of mediation can not be applied to bankruptcy cases because bankruptcy is included in the volunteer domain whereas mediation in court is implemented in contentiosa case. Therefore, peace in the settlement of bankruptcy cases can’t be executed at the beginning of the investigation of bankruptcy cases in the Commercial Court, as new peace can be applied if the debtor's status is clear as a bankrupt party. Although mediation can’t be implemented in order to achieve peace in the bankruptcy case in the Commercial Court, the concept of a win-win solution remains in the implementation of peace in the Commercial Court is apeace that can provide balanced benefits for both parties as business actors.Keywords: bankruptcy, peace, win-win Solution